Social participation of national service training program of Leon National College of Agriculture - Tacardon, May Flor M (University of the Philippines Visayas, 2019)
By the virtue of Republic Act 9163, otherwise known as the "National Service Training Program (NSTP) Act of 2001", NSTP was instituted in all tertiary education institutions in the Philippines. It is a civic education and defense preparedness program designed to promote the sense of community service and boost the spirit of patriotism among the youth. Since its implementation, most tertiary institutions have not assessed its outcomes. Hence, this present study assessed the social participation of the NSTP Graduates of Western Visayas College of Agriculture-Leon National College of Agriculture (WVCST-LNCA). The researchers allowed the 154 respondents to answer the Self-administered Questionnaire (SAQ). This SAQ was validated by the experts in the field of social science and research. The qualitative data were analyzed using thematic analysis while the quantitative data were analyzed using descriptive statistical tools. Findings of the study revealed that the main experiences of the NSTP students in the program include activities related to environmental protection, social awareness, health, and developing citizenship. Graduates have developed both positive and negative impressions about their experiences. After taking the courses, graduates have been active in involving themselves in various civic endeavors such as environmental pprotection and conservation activities, volunteering programs, community programs, and health activities. However, their level of political activity was found out to be very low. This condition may be attributed to the presence of some diversions such as social media, sport activities, and vices. Thus, this study recommends the integration of political activity in NSTP alongside issues fo gender and equality, respect for human dignity, and environmental protection to promote tolerance among students.